The Use Of First Language In Teaching Speaking For TheSecond Grade Students Of Marketing Department At SMK N 1 Banyudono In 2013/2014 Academic Year - Febrianingrum, Ade; , Mauly Halwat Hikmat, Ph. D; , Aryati Prasetyarini, M.Pd (2014)
This research paper is intended to describe the use of first language in teaching speaking for the second grade students of marketing department at SMK N 1 Banyudono in 2013/2014 academic year. The source of the data are the English teacher and the students of XI Marketing 2 at SMK N 1 Banyudono. In research paper, the writer uses two instruments to collect the data, namely : observation and interview. The data consists of information about the functions, factors, and the students' perception to the use of first language by the teacher in teaching speaking. Based on the data analysis, the writer gets 173 data of L1 used by the teacher in teaching speaking. The writer classifies them into 17 functions. The functions of L1 are mostly for joking 13,87%. Only 0,53% L1 is used to manage the classroom. The finding also shows that there are 17 factors why the teacher uses L1. The highest precentage is making the students enjoy the material and help learners to be stress-free (13,87%). The lowest percentage is managing the classroom (0, 58%). Based on the students' perception, the use of L1 by the teacher has some functions, namely (1) explaining the material (2) giving correction (3) explaining the homework (4) explaining the task (5) telling the teacher's past (6) joking (7) explaining grammar. As for the factors' perceptions causing the teacher uses L1, the factors can be classified into 7 factors: (1) to make the students understand the explanation of material, task, and homework (2) to make the students understand when the teacher explain in English (3) to decrease the students' shyness to speak (4) to correct students answer (5) to make the students relax and enjoy to study (6) to make the students are not bored.